Translation for Performance: Biblical Performance Criticism in Bible Translation - Jeanette Mathews (Religions)
Biblical Scholars working with ancient texts are engaged in the daily task of Bible translation. A commitment to Biblical Performance Criticism (BPC) can be transformative in the task of translation. It is argued in this paper that responsible translation will work towards replicating the artistry of original transmitters of texts in order to draw out traces of the original orality embedded in the texts. Examples of performance-sensitive translations of texts predominantly from the Hebrew Bible are provided. This e-paper also demonstrates that translations that draw out performative elements contribute to interpretation, especially when such scripts are staged before audiences. Subsequent analysis of the performance including audience response contributes to such interpretation. Performance-sensitive translation and actual performance thus become tools for embodiment and the interpretation of biblical texts in our own time.